2005
DOI: 10.1161/01.atv.0000172626.00296.ba
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Inducible Nitric Oxide Synthase–Mediated Vascular Dysfunction

Abstract: Objective-Inducible nitric oxide synthase (iNOS) is expressed in arteries during inflammation and may contribute to vascular dysfunction. Effects of gene transfer of iNOS to carotid arteries were examined in vitro in the absence of systemic inflammation to allow examination of mechanisms by which iNOS impairs contraction and relaxation. Methods and Results-After gene transfer of iNOS with an adenovirus (AdiNOS), constrictor responses to phenylephrine (PE) and U46619 were impaired. After AdiNOS, inhibition of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 46 publications
3
91
0
4
Order By: Relevance
“…Despite having a common end product (NO), activating different types of NOS can have very different effects on renal tissue, depending on both the temporal profile and topography of NO production by each NOS enzyme (42). iNOSderived NO appears to participate in vascular dysfunction (55,56), and it is therefore thought that NO generated by iNOS is harmful, leading to tissue damage (43,55,57). Several in vivo and in vitro investigations have demonstrated that inhibiting the expression or activity of iNOS (58,59) or even the absence of iNOS itself (60) can prevent renal I/R injury.…”
Section: Microvascular Dysfunction and The Balance Between Vasoconstrmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite having a common end product (NO), activating different types of NOS can have very different effects on renal tissue, depending on both the temporal profile and topography of NO production by each NOS enzyme (42). iNOSderived NO appears to participate in vascular dysfunction (55,56), and it is therefore thought that NO generated by iNOS is harmful, leading to tissue damage (43,55,57). Several in vivo and in vitro investigations have demonstrated that inhibiting the expression or activity of iNOS (58,59) or even the absence of iNOS itself (60) can prevent renal I/R injury.…”
Section: Microvascular Dysfunction and The Balance Between Vasoconstrmentioning
confidence: 99%
“…Incomplete restoration of endothelium-dependent vasodilation, however, suggests that other pathways could be involved in this dysfunction, such as prostaglandins or endotheliumderived hyperpolarizing factor (EDHF) (66,67). Furthermore, during I/R, a lack of tetrahydrobiopterin (BH4)-an essential cofactor of NOS-has also been implicated in endothelial dysfunction after I/R injury (56). Deficits in BH4 lead to eNOS uncoupling and the oxidation of O 2 , which causes the enzyme to produce superoxides and generate peroxynitrite instead of NO (68).…”
Section: Microvascular Dysfunction and The Balance Between Vasoconstrmentioning
confidence: 99%
“…14 PHE responses were diminished after transfection of iNOS enzymes into blood vessels. 15 Blood vessels stimulated with lipopolysaccharide have diminished responses to ACH due to inducible nitric oxide synthase (iNOS) activity 15 and both PHE and ACH responses could be partially reversed by selective iNOS inhibitors indicating that NOS enzymes, excess NO, and oxidative species interfere with both contractile and dilatory responses. Upregulation of iNOS enzymes in response to inflammation results in excessive nitric oxide production, consumption of tetrahydrobiopterin (BH 4 ), and decreased NO production by other NOS enzymes including endothelial derived NOS (eNOS), which is responsible for many endothelial dependent vasodilatory responses.…”
mentioning
confidence: 99%
“…The latter was illustrated in the rabbit carotid arteries where virally encoded murine inducible NO synthase (iNOS) was expressed 20-24 h after infection of arterial rings [13]. The tissues were mounted after culture and displayed the expected NO-mediated nonspecific inhibition of contractile responses.…”
Section: The Contractility Assay and Its Variantsmentioning
confidence: 99%